Research on High Quality Evaluation and Influencing Factors of China Energy Finance: Evidence From A-Share New Energy Companies - Sheng, Zeng; Yuan, Gao; Xiru, Deng; Minglong, Zhang; Yi, Wu; Yu, He (Frontiers in Environmental Science, 2021)
High-quality development of energy finance (HQDEF) is not only a key component of high-quality economic development, but also an important solution to the current difficulties of China’s energy industry, such as environmental pollution and supply security. This study first clarifies the connotation and mechanism of high-quality energy finance, and then uses static super-efficiency DEA model as well as dynamic Malmquist index to evaluate the HQDEF from the perspective of input and output. We find that the overall effect of the HQDEF is at a low level. The scale efficiency and technical efficiency are deviating, where the former (latter) continues to expand (decline). The dynamic Malmquist index shows a slight decline in the efficiency of the HQDEF. Further studies on five dimensions of the HQDEF show that innovation has the highest correlation with each new energy industry. Lacking of innovation is the main bottleneck that restricts the development of the current new energy industry. The correlations among different industries have a tendency of ‘symmetry’ and ‘convergence’. Our study provides countermeasures and suggestions for the high-quality and stable development of China’s energy finance from the perspectives of optimizing the financial support structure, building a technological innovation platform, optimizing the industrial structure, rationally making green investments and open development.